2012
DOI: 10.1093/eurpub/cks097
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress during pregnancy is related to adverse birth outcomes: results from a large multi-ethnic community-based birth cohort

Abstract: Babies from pregnant women reporting both high levels of anxiety and depressive symptoms are at highest risk for adverse birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 28 publications
5
121
0
8
Order By: Relevance
“…Previous studies supports this suggestion as their studies also revealed that request for caesarean sections were higher among pregnant women particularly nulliparous with more childbirth fears (Fenwick et al, 2009;Hall et al, 2012;Handelzalts et al, 2012;Laursen et al, 2009;Nieminen et al, 2009;Rubertsson et al, 2014). Evidences also established the relationship between high levels of pregnancy anxiety and adverse labour outcomes such as preterm births, low birth weight and mode of delivery (Catov et al, 2010;Hernandez-Martinez et al, 2011;Loomans et al, 2013;Rauchfuss & Maier, 2011). So current study recommend that the prenatal care should focus on measures to reduce pregnancy specific anxiety particularly among nulliparous women which would reduce adverse pregnancy outcomes.…”
Section: Childbirth Anxietysupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies supports this suggestion as their studies also revealed that request for caesarean sections were higher among pregnant women particularly nulliparous with more childbirth fears (Fenwick et al, 2009;Hall et al, 2012;Handelzalts et al, 2012;Laursen et al, 2009;Nieminen et al, 2009;Rubertsson et al, 2014). Evidences also established the relationship between high levels of pregnancy anxiety and adverse labour outcomes such as preterm births, low birth weight and mode of delivery (Catov et al, 2010;Hernandez-Martinez et al, 2011;Loomans et al, 2013;Rauchfuss & Maier, 2011). So current study recommend that the prenatal care should focus on measures to reduce pregnancy specific anxiety particularly among nulliparous women which would reduce adverse pregnancy outcomes.…”
Section: Childbirth Anxietysupporting
confidence: 64%
“…The results from a large-multi ethnic community-based study in Amsterdam involving 7740 pregnant women revealed that pregnancy anxiety was related with adverse labour outcomes such as preterm and low birth weight (Loomans, van Dijk, et al, 2013). Catov et al (2010) conducted a prospective longitudinal study among 667 African American pregnant women revealed that maternal anxiety was associated with increased risk of preterm birth and low birth weight.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotional distress has been related to poor obstetric outcomes such as preterm birth and low birth weight (Dunkel Schetter, 2012;Goedhart, 2010;Graignic-Philippe, Dayan, Chokron, Jacquet, & Tordjman, 2014;Loomans et al, 2013). Regarding long-term effects, there is growing evidence that maternal distress during pregnancy might interfere with infant development up until adolescence (Van den Bergh, Mulder, Mennes, & Glover, 2005;Dorrington et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Depression, anxiety and pregnancy-related anxiety are the most frequent occurring psychological signs and symptoms that construct maternal distress, varying in severity [1]. Prevalence rates of maternal distress among Dutch healthy pregnant women vary from 2 % to 30 % [3][4][5][6][7][8][9][10][11][12][13][14] measured with psychometric measures of depression and/ or (pregnancy-related) anxiety with scores above set cut-off points. Maternal distress can be caused by either pregnancy itself or non-pregnancy related factors [1][2][3].…”
Section: Introductionmentioning
confidence: 99%